2017
DOI: 10.1111/jog.13373
|View full text |Cite
|
Sign up to set email alerts
|

Current status of non‐invasive prenatal testing in Japan

Abstract: Aim The purpose of this study was to report the 3‐year experience of a nationwide demonstration project to introduce non‐invasive prenatal testing (NIPT) of maternal plasma for aneuploidy, and review the current status of NIPT in Japan. Methods Tests were conducted to detect aneuploidy in high‐risk pregnant women, and adequate genetic counseling was provided. The clinical data, test results, and pregnancy outcomes were recorded. We discuss the problems of NIPT on the basis of published reports and meta‐analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 38 publications
2
47
0
1
Order By: Relevance
“…By comparison, the prenatal screening rates in other advanced countries are reportedly as follows: less than 30% in the Netherlands, 74% in the United Kingdom, and more than 90% in Denmark (Crombag et al, ; Vassy, Rosman, & Rousseau, ). As in other countries, NIPT has become available in Japan (Sago & Sekizawa, ; Samura et al, ). With this increasing availability of prenatal genetic testing in Japan, a higher population of DS fetuses would be detected and the equipoise of DS live births at present might be broken.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the prenatal screening rates in other advanced countries are reportedly as follows: less than 30% in the Netherlands, 74% in the United Kingdom, and more than 90% in Denmark (Crombag et al, ; Vassy, Rosman, & Rousseau, ). As in other countries, NIPT has become available in Japan (Sago & Sekizawa, ; Samura et al, ). With this increasing availability of prenatal genetic testing in Japan, a higher population of DS fetuses would be detected and the equipoise of DS live births at present might be broken.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that many pregnant women were most concerned about the safety of their children Pregnant women aged 35 years or older and those with evidence of chromosomal abnormalities could participate in the study. Based on a recent report, 61,330 tests were performed over a 3-year period [14]. Since the need for prenatal diagnosis for pregnant women continued to grow, the JSOG announced that the availability of NIPT would be extended to general obstetrical clinics in 2019 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Over 60 000 tests were performed by the Japan NIPT consortium in the first 6 years since its introduction, with more than 90% of cases analyzed via massively parallel sequencing (s‐MPS) for the DNA analyses. Among the pregnant women tested, 1.8%, 97.9%, and 0.3% obtained positive, negative, and inconclusive results, respectively . The positive predictive value of trisomy 21 was over 96%, and the negative predictive value of three trisomies was <1 in 10 000 .…”
Section: Introductionmentioning
confidence: 91%
“…Among the pregnant women tested, 1.8%, 97.9%, and 0.3% obtained positive, negative, and inconclusive results, respectively . The positive predictive value of trisomy 21 was over 96%, and the negative predictive value of three trisomies was <1 in 10 000 . Previously, we conducted NIPT analysis of cfDNA in maternal plasma comprising maternal and placental DNA, and the median fetal fraction of samples having euploid results was 13.7% .…”
Section: Introductionmentioning
confidence: 95%